Irony, deception and theory of mind in people with intellectual disabilities and dual diagnoses - Djordjević, Mirjana; Glumbić, Nenad; Brojčin, Branislav (Vojnosanitetski pregled, 2021)
Background/Aim. The ability to comprehend and produce irony and deception is rarely explored in people with intellectual disability (ID) or dual diagnoses (DD). The ability to understand irony and deception appears to be related to many cognitive skills, but some authors point out that the theory of mind is one of the most important factors for this ability. This research was conducted to determine the linguistic aspects of production and comprehension of irony and deception in adults with ID and DD, as well as the relationship of these abilities with theory of mind. Methods. The sample consisted of 120 people with ID aged between 20 and 56. Half of the sample comprised people with DD. Four subscales from the Assessment Battery for Communication were used to assess the participants’ abilities to produce and comprehend irony and deception. False-belief tasks from “appearance-reality” category were used in theory of mind assessment. The level of intellectual functioning was measured by the Raven’s progressive matrices, while the Peabody Picture Vocabulary Test was used to assess speech comprehension ability. Results. The results show that participants with DD and ID comprehend and produce false statements better than ironic ones. Participants with ID were more successful in production than in comprehension tasks of both false and ironic statements, while the same was true for participants with DD only for ironic statements. Participants with ID were significantly more successful than participants with DD in irony comprehension tasks. In participants with ID, first-order theory of mind significantly correlated only with the ability to produce irony, and second-order theory of mind significantly correlated with producing irony and deception. There were no significant correlations between theory of mind and producing and comprehending irony and deception in participants with DD. Conclusion. Although differences in some aspects of assessed abilities were found between the two groups of participants, the similarities in the profile of these abilities were dominant. Results of variability can be explained by differences in speech comprehension ability more than by differences in nonverbal intellectual functioning or theory of mind acquisition. Future studies should assess the influence of other cognitive factors.